An assessment of ethnic and environmental influences on the phenotypes of hypertension. (14th October 2021) - Iyeku, A C; Jalaludeen, N; Ojji, D B; Cheriyan, J; McEniery, C M; Wilkinson, I B
Abstract: Background: Hypertension is a growing global concern with developing countries now having the highest prevalence. Environmental factors such as socioeconomic status and diet, together with ethnicity-related factors may influence the development of hypertension and its complications such as left ventricular hypertrophy (LVH). However, the relative contributions of environment and ethnicity to these outcomes remain poorly understood. Purpose: To test the hypothesis that black hypertensives living in Nigeria would have a higher prevalence of hypertensive target organ damage (i.e. LVH and dysfunction) compared with black hypertensives living in the UK. Methods: We conducted a three-arm comparative study based on self-defined ethnicity and country of residence. We carried out detailed cardiovascular phenotyping in untreated Black hypertensives (n=53) living in Nigeria (BNig), untreated Black (BUK) hypertensives (n=25), and untreated White (WUK) hypertensives (n=59) living in the UK. We measured brachial and central blood pressure and undertook 2D echocardiography in all the participants. In addition, we collected serum and 24-hour urine biochemistry. Results: The three groups had similar mean age and BMI (Table 1). The BNig group had significantly higher brachial SBP (P=0.01) and LV mass index (LVMI); P<0.001) compared with the BUK group. Furthermore, both BNig & BUK groups each had significantly higher brachial SBP (BNig: 162mmHg, BUK: 151mmHg) and LVMI (BNig: 100.9g/m 2, BUK:86.4 g/m 2 ) compared with the WUK group (Brachial SBP: 144mmHg, LVMI: 82.2g/m 2 ). The prevalence of concentric LVH was similar in the two UK groups (BUK: 10%, WUK: 12%) but higher in the BNig group (41%). Septal early diastolic velocity was significantly lower in BNig group (7.0cm/s) compared to BUK (10.0cm/s) and WUK (10.0 cm/s). After adjusting for 24-hour sodium, brachial SBP (162mmHg) in the BNig group was still significantly higher compared with the other two groups [F(2, 109)=13.805, BK (151mmHg, P=0.032), White UK (145mmHg, P<0.001)). However, after controlling for SBP, difference in LVMI persisted only between the BNig (EMM: 98.4 g/m 2 ) versus WUK (EMM: 84.2 g/m 2 ) groups, with no significant difference in BNig vs BUK (86.6g/m 2, P=0.156) [F(2, 128)=4.245, p=0.016]. Conclusion: Our data suggest that higher SBP and salt intake do not explain all of the environmental differences in the prevalence of LVH and LV dysfunction in hypertensive patients drawn from different ethnicities and environments, suggesting that other factors are likely to play an important role. Further work is in a larger group is required to confirm these findings. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Niger Delta Development Commission